Impact of Tocilizumab on Clinical Outcomes in COVID-19-Associated Cytokine Release Syndrome: A Single-Center Experience. (April 2023) - Raja, Karan; Daniel, Nicole; Morrison, Susan; Patel, Ruben; Gerges, Jessica; Nadeem, Komal; Chen, Brandon; Kang, Soo; Patel, Mitesh; Beggs, Donald; Attalla, Mark; Ballem, Naveen; et al.
Background: Tocilizumab is an interleukin-6 receptor antagonist hypothesized to blunt the uncontrolled immune response, cytokine release syndrome, in severe COVID-19 and prevent attributable morbidity and mortality. Objective: The objective of this study was to assess the impact of tocilizumab on clinical outcomes in COVID-19-associated cytokine release syndrome. Methods: Single-center, retrospective cohort study assessing sixty-nine adult patients receiving tocilizumab for suspected COVID-19 cytokine release syndrome. The primary outcome was change in WHO clinical status scale on day seven post-dose analyzed using the Wilcoxon signed rank test. Secondary outcomes assessed impact of timing of administration on clinical outcome. Safety analyses included development of neutropenia, thrombocytopenia, transaminitis, and sepsis within 7 days post-dose. Statistical analyses were conducted using Microsoft Excel. Results: No aggregate clinical change was found between day 0 and day 7. Eleven patients improved, twenty-seven worsened, and thirty-one showed no change. Clinical outcomes were weakly correlated with time from symptom onset (rs = 0.21; p = 0.08) or hospital admission (rs = -0.08; p = 0.49) to dose. In-hospital mortality was 63%. Sepsis was diagnosed in 21 patients, five of which were post-dose. Transaminitis, neutropenia, and thrombocytopenia occurred in seven, one, and six patients, respectively. Conclusion: Tocilizumab did not appear to influence clinical outcomes in our study population, irrespective of timing of administration. Adverse events were not considered drug-related.